2017
DOI: 10.21010/ajtcam.v14i5.18
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Dichrocephala Integrifolia (Asteraceae) in a Mouse Model of Monosodium Glutamate-Induced Neurotoxicity

Abstract: Background: In Africa, neurodegenerative diseases in the elderly have become a major health concern due to the increase in live expectancy. Glutamate mediated neurotoxicity is involved in neurodegenerative diseases such as Ischemia, Epilepsy, Alzheimer's and Parkinson diseases. Plants with antioxidant properties are reported to protect vital organs against glutamate toxicity. This study aims to assess the effect of Dichrocephala integrifolia against monosodium glutamatemediated neurotoxicity and oxidative stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Even though the investigations of these authors were at the level of the liver, a previous study has also shown that D. integrifolia protects brain against D-galactose-induced oxidative damage through its anti-oxidant properties [ 37 ]. The anti-oxidant properties of this plant are due to the presence of some chemical compounds such as flavonoids, tannins, and anthraquinones [ 43 ]. Growing lines of evidence have linked brain oxidative stress and neuroinflammation to ethanol toxicity [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the investigations of these authors were at the level of the liver, a previous study has also shown that D. integrifolia protects brain against D-galactose-induced oxidative damage through its anti-oxidant properties [ 37 ]. The anti-oxidant properties of this plant are due to the presence of some chemical compounds such as flavonoids, tannins, and anthraquinones [ 43 ]. Growing lines of evidence have linked brain oxidative stress and neuroinflammation to ethanol toxicity [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Brain nitric oxide level was measured in the brain using the Greiss reagent [ 43 , 44 ]. Briefly, 0.5 mL of Greiss reagent and 0.5 mL of brain's supernatant were introduced into a test tube and allowed to stand for 5 minutes, after which the absorbance of the mixture was read at 540 nm using a spectrophotometer (Thermo Scientific; MultiskanTM FC Microplate Photometer).…”
Section: Methodsmentioning
confidence: 99%
“…Thirty minutes after MSG injection, rats were noticed for any sign of fighting, aggressiveness and hyperactivity or calmness. Rats were scored 0 when they exhibited calmness, and scored 5 for fighting and aggressive behaviors (Nadège et al 2017).…”
Section: General Observations (Aggressivity)mentioning
confidence: 99%